2014
DOI: 10.1111/ssqu.12134
|View full text |Cite
|
Sign up to set email alerts
|

The Political CEO: An Event Study Comparing Consumer Attributions of CEO Behavior*

Abstract: Objective. We sought to establish a relationship between negative political behavior of key firm members and consumer evaluations of the firm through an attribution theories extension. Method. We sample and code approximately 1,500 Tweets surrounding Dan Cathy's political beliefs about marriage and Taco Bell's response to a lawsuit regarding beef. Results. Consumers are more likely to attribute a volitional event (CEO political disapproval) toward the firm than toward societal elements. However, consumers expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
(53 reference statements)
3
18
0
Order By: Relevance
“…With respect to the event study analysis, we observe that a company's stock price gains a statistically significant abnormal return of 2.68% in the four days immediately following news of its support for the campaign, which suggests that market participants positively viewed the decision to join the campaign. This finding corroborates those of Dodd and Supa (2014, 2015), Mikeska and Harvey (2015) and Chatterji and Toffel (2019), who found that corporate stances on social issues significantly impact financial performance, as measured by consumer purchase intention.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…With respect to the event study analysis, we observe that a company's stock price gains a statistically significant abnormal return of 2.68% in the four days immediately following news of its support for the campaign, which suggests that market participants positively viewed the decision to join the campaign. This finding corroborates those of Dodd and Supa (2014, 2015), Mikeska and Harvey (2015) and Chatterji and Toffel (2019), who found that corporate stances on social issues significantly impact financial performance, as measured by consumer purchase intention.…”
Section: Discussionsupporting
confidence: 90%
“…That is, a commitment to actively engage and align with social causes that affect a broader group of stakeholders can improve financial performance. For example, CSA efforts can positively impact financial performance through consumers' purchasing intent, altruistic values and positive brand perception, all of which may increase the likelihood of consumers choosing the products of businesses that share their values (Dodd and Supa, 2014; Mikeska and Harvey, 2015; Chatterji and Toffel, 2019; Park and Jiang, 2020) [5]. Promoting values that they care about may also help firms to attract employees who are more motivated to perform, in part because of the opportunity to contribute to substantial social change.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerous studies have examined corporate campaign contributions (e.g., Ansolabehere, Figueiredo, & Snyder, 2003), lobbying (e.g., Hillman, Keim, & Schuler, 2004), and CSR (e.g., Margolis & Walsh, 2003), we know of no research that has directly explored CEO activism, although two recent studies found that consumers’ willingness to buy products and services might be affected by whether they support the political and social stances associated with the firm (Dodd & Supa, 2014; Mikeska & Harvey, 2015). Our study focuses on the role of individual leaders and not only examines the influence of CEO activism on purchasing intent, but also compares the influence that business and political leaders’ social statements have on public opinion on a given issue.…”
Section: Motivationmentioning
confidence: 99%